1887 Ala. Code 93, § 4094 - (:unkn) unknown (My University, 1887)
Prohibited use of a firearm while fighting in any city, town, militia muster, or public place. Violators fined not less than two hundred, nor more than five hundred dollars, or imprisoned in jail, or sentenced to hard labor not exceeding six months.
Keywords: DUELING